Pemberdayaan Kader dalam Pencegahan Stunting - Tintin Sumarni; Aini Yusra; Abd. Gafar; Gusnedi; Firwandri Marza; Deharnita (CV. CENDIKIA JENIUS INDONESIA, 2026)
Stunting remains a chronic nutritional problem that requires the active involvement of health cadres as the frontline workers in Integrated Health Posts (Posyandu). This community service program aimed to improve the knowledge, motivation, and skills of health cadres in preventing stunting in Kampung Jawa Village, Solok City. The participants were 47 health cadres who attended a training session on July 30, 2025, at PAUD Kasih Mama. The implementation methods included preparation, educational sessions using lectures and discussions, practical training on measuring body weight and height, recording data in the Maternal and Child Health (MCH) handbook, and monitoring and evaluation through a knowledge test. The results showed that 81.0% of cadres had good knowledge, while 19.0% had low knowledge. All cadres (100%) were able to perform anthropometric measurements, record data in the MCH handbook, and provide education to mothers of toddlers at Posyandu. In conclusion, cadre empowerment effectively improved the capacity of health cadres in stunting prevention and should be implemented continuously to support the acceleration of stunting reduction in Solok City.